1991
DOI: 10.1111/j.1365-2230.1991.tb00396.x
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of various methods and antigens for the detection of antibodies against Pityrosporum ovale in patients with seborrhoeic dermatitis

Abstract: Sera from 10 patients with seborrhoeic dermatitis and from 10 age-matched healthy individuals were examined for IgG activity against Pityrosporum ovale. The IgG activity was analysed using the following techniques: an enzyme-linked immunosorbent assay (ELISA) against whole P. ovale cells, purified cell-wall carbohydrate or protein extract, an indirect slide-immunofluorescence assay and fluorescence-activated flow cytometry using the whole organism as antigen. The ELISA method using the protein antigen was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…17 Bergbrant et al found no difference between Malassezia-specific antibody levels in such groups with four of five assay methods, although one of their assays showed a marginally reduced antibody level in the patient group. 18 Kieffer et al found no evidence of IgE antibody to Malassezia in seborrhoeic dermatitis and only occasional reactions in healthy controls. 19 Ashbee et al found that total blood lymphocyte counts in patients with seborrhoeic dermatitis were indistinguishable from those in healthy subjects, as were the proportion of their lymphocytes expressing CD4 and CD8 markers, the numbers of circulating B cells, and the levels of total serum immunoglobulins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…17 Bergbrant et al found no difference between Malassezia-specific antibody levels in such groups with four of five assay methods, although one of their assays showed a marginally reduced antibody level in the patient group. 18 Kieffer et al found no evidence of IgE antibody to Malassezia in seborrhoeic dermatitis and only occasional reactions in healthy controls. 19 Ashbee et al found that total blood lymphocyte counts in patients with seborrhoeic dermatitis were indistinguishable from those in healthy subjects, as were the proportion of their lymphocytes expressing CD4 and CD8 markers, the numbers of circulating B cells, and the levels of total serum immunoglobulins.…”
Section: Discussionmentioning
confidence: 97%
“…Malassezia-specific antibody can be detected in the sera of all adults but the quantity is very variable. [16][17][18][19][20] Midgley and Hay found a slightly greater mean level of Malassezia-specific IgG in patients with seborrhoeic dermatitis than in healthy subjects. 16 Ashbee et al found no difference in total Malasseziaspecific antibody, or immunoglobulin subclasses, between patients with seborrhoeic dermatitis and controls.…”
Section: Discussionmentioning
confidence: 99%
“…12 The humoral immune response to Malassezia in patients with seborrhoeic dermatitis and pityriasis versicolor has been studied using different antigen preparations and different techniques: elevated titres in patients compared with controls, as well as no differences in titres, have been reported. [13][14][15][16][17][18] A cell-mediated immune response to Malassezia has been demonstrated by lymphocyte transformation tests in healthy individuals. 19 Lymphocyte transformation in patients with pityriasis versicolor and in patients with seborrhoeic dermatitis has been reported with divergent results.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of different methods and different antigen prep- (50). Comparing combinations of various methods and antigens, the only combination able to find a significant difference in antibody titers between SD patients and controls was an ELISA using a cell wall protein antigen.…”
Section: Seborrheic Dermatitis and Dandruffmentioning
confidence: 99%